Implication of Parents in the Educational System: An Analysis of Spanish Legislation - Granda-Piñán, Amelia (International Journal about Parents in Education, 2023)
A correct parents’ involvement in their children’s education has a undeniable importance. Many aspects need parents’ commitment and a tight collaboration between parents and school in order to be able to achieve a comprehensive development of the child. Numerous authors agree with the great importance a correct action and cooperation have. Due to this importance, legal documents define the parents’ rights and privileges as well as their duties, establishing also the procedures schools should follow to implicate parents in their children education. After accomplish a detailed analysis of the educational legislation in force in Spain, and more concretely in the Valencia Community, we have concluded that the relationship of parents and schools is based in three main aspects that are clearly defined: information, participation and cooperation.. Knowing how to cope with the three of them would contribute to get a better quality in education. Spanish legislation demarcates the field of action of schools and parents. On the one hand, parents should know what legislation allows them to do in the educational formal system and how to do it. On the other hand, teachers should know what obligations they have and how they should let parents collaborate in formal education.